456 Assessing the Efficacy of the mJOA in Myelopathic Patients: A Cervical QOD Study. (1st April 2022) - Yee, Timothy J.; Upadhyaya, Cheerag D.; Coric, Domagoj; Potts, Eric A.; Bisson, Erica F.; Turner, Jay D.; Knightly, John J.; Fu, Kai-Ming G.; Foley, Kevin T.; Tumialan, Luis M.; Shaffrey, Mark E.; Bydon, Mohamad; et al.
Abstract : INTRODUCTION: The modified Japanese Orthopedic Association (mJOA) score is a validated metric for assessing severity of myelopathy. However, its relationship to functional and quality-of-life outcomes after surgery is incompletely known. METHODS: The cervical module of the prospectively enrolled Quality Outcomes Database (QOD) was queried. Patients over age 18 who underwent single-stage surgery for CSM were included. Revision and operations for infection, trauma, and tumor were excluded. Postoperative outcomes included the modified Japanese Orthopedic Association (mJOA) score, the Neck Disability Index (NDI), and Quality-Adjusted Life Year (QALY) by EQ-5D. Improvement in mJOA was used as the independent variable in univariate and multivariate linear regression. RESULTS: Across 14 surgical centers, 1, 121 patients were identified. Mean age±SD was 60.6±11.8 years, and 52.5% were male. Anterior-only operations were performed in 772 patients (68.9%), and posterior-only operations in 349 patients (31.1%). Mean mJOA±SD scores at baseline, 3 months postoperatively, and 12 months postoperatively were 12.0 ± 2.8 (n = 1121), 13.9 ± 2.6 (n = 914), and 13.8 ± 2.8 (n = 801). Mean NDI ± SD scores at baseline, 3 months postoperatively, and 12 months postoperatively were 38.3 ± 20.8 (n = 1117), 23.1 ± 17.9 (n = 942), and 20.4 ± 19.4 (n = 807). Mean QALY ± SD scores at baseline, 3 months postoperatively, and 12 months postoperatively were 0.6 ± 0.2 (n = 1029), 0.7 ± 0.2 (n = 899), and 0.7 ± 0.2 (n = 761). By univariate analysis, improvements in mJOA were associated with improvements in NDI and QALY at 3 and 12 months postoperatively (all p < 0.0001). These findings were similar in multivariate analysis. CONCLUSION: In this large cohort of patients who underwent surgery for CSM, improvements in mJOA were associated with improvements in NDI and QALY. These findings suggest that changes in mJOA can serve as a proxy for functional and quality-of-life outcomes.